Der Hopfenanbau in der Provinz Léon (Spanien) - Eine Diffusionsanalyse - Breuer, Toni (ERDKUNDE, 1979)
The subject under investigation is the diffusion of hop cultivation in the Leon Province over the period 1950-1972. Cultivation is carried out by small agricultural enterprises which have taken up hop cultivation in a situation of relative distress. - i.e. when subjected to economic pressure. Since hop cultivation is conducted on a contractual basis, two different steering mechanisms meet in the process of diffusion: the determining influence of the institution which offers the contracts, and the neighbourhood effect in the sense of an invitation to follow suit. This gives rise to two different types of innovation centres.